2022
DOI: 10.3389/fphys.2022.973461
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to dim light at night alters daily rhythms of glucose and lipid metabolism in rats

Abstract: Nocturnal light pollution has been rapidly increasing during the last decades and even though dim artificial light at night (ALAN) has been associated with metabolic diseases, its mechanism is still far from clear. Therefore, the aim of our study was to thoroughly analyze the effects of ALAN on energy metabolism, metabolites, metabolic hormones, and gene expression. Male Wistar rats were kept in either the standard light:dark (12:12) cycle or exposed to ALAN (∼2 lx) during the whole 12-h dark phase for 2 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 66 publications
0
18
0
Order By: Relevance
“…This difference between groups is most likely determined predominantly by mothers. In our recent study with mature male rats [ 14 ], the same intensity of ALAN eliminated daily oscillations of plasma metabolites in the ALAN but not in the CTRL group. To our knowledge, no studies dealing with the rhythmicity of hormones and metabolites in pregnant females exposed to ALAN are available, requiring further research.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This difference between groups is most likely determined predominantly by mothers. In our recent study with mature male rats [ 14 ], the same intensity of ALAN eliminated daily oscillations of plasma metabolites in the ALAN but not in the CTRL group. To our knowledge, no studies dealing with the rhythmicity of hormones and metabolites in pregnant females exposed to ALAN are available, requiring further research.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies suggest that a low intensity of ALAN lasting all night can interfere with vital physiological [ 11 ] and neural processes in humans [ 12 ]. Molecular mechanisms mediating the negative effects of ALAN are explored in animal experiments and include disruption of the circadian rhythms in metabolism [ 13 , 14 ], sleep [ 15 ], or the immune system [ 16 , 17 ]. The developmental aspects of chronodisruption have been less studied compared to mature animals and humans but can be important because maternal shift work can have negative consequences for offspring [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence provided by experimental studies has demonstrated that dim ALAN (≤5 lx) can compromise circadian coordination in laboratory rodents. The rhythmic profile of locomotor activity was preserved in rats exposed to dim ALAN for 2 weeks, but mean night-time levels were reduced, and daytime activity was increased compared to controls [ 127 ]. Another study in rats reported that dim ALAN diminished the power of 24 h activity rhythm and induced a second approximately 25 h free-running rhythm, indicating internal desynchronization of locomotor activity [ 128 ].…”
Section: Effects Of Circadian Disruption On Innate Immunitymentioning
confidence: 99%
“…In the SCN, dim ALAN exposure clearly suppressed the daily rhythms of clock genes in both rats [ 129 , 130 ] and mice [ 131 , 132 ]. In peripheral tissues, clock gene rhythms appeared to be less affected by ALAN than in the master oscillator, though they showed lowered amplitude or shifts in acrophase [ 127 , 129 , 131 ]. The daily plasma melatonin rhythm was eliminated in rats after 2 weeks of dim ALAN (2 lx) exposure due to suppressed nocturnal melatonin levels [ 129 ], which were also reported in other studies, not only in rats [ 133 , 134 ] but also in diurnal birds [ 135 , 136 ] and humans [ 137 ].…”
Section: Effects Of Circadian Disruption On Innate Immunitymentioning
confidence: 99%